Dynamics of sediment transport in two subtropical plain rivers of South America - Orfeo, Oscar (2006)
Two rivers located in the subtropical Chaco</place /> plain are compared in order to analyse the sediment transport dynamics. Gauging and sediment samples were obtained during different hydrological stages. Grain size and textural parameters were obtained for the bed material. Concentration and transport of suspended sediment were also determined. In the Bermejito</placename /> River basin</placetype /></place />, the downstream increment of the discharge generates a predictive response in the sandy bed sediment. Discharge and suspended sediment load show a direct correlation. The Tapenagá</placename /> River</placetype /></place /> headwaters, composed mainly of fine sediments, are in extensive wetlands with deficient runoff. The sand content of the bed sediment increases constantly towards its confluence with the Parana River</place />, owing to the erosion of old sandy river deposits. Although the concentration of suspended sediment maintains an inverse correlation with discharge, the suspended load increases downstream. In the lower course of this river the aquatic vegetation plays an important role because plants colonize the fluvial system during lower water periods, producing abundant organic matter. At the beginning of the flood period, the deposited fine material is rapidly re-suspended, generating a sudden increase of the wash load concentration together with the discharge increment. During the flood, there is no deposition over the clay-rich bed in the highlands, while the bed becomes increasingly composed of sands in the lower course.